Zad 1 Wykonaj dodawanie i zredukuj wyrazy podobne:

a. 3ax + (2ax-5) =
b. -4x + ( -2x+3y-3)=
c. ( x-2y) + ( 5x-7y) =
d. ( 2a+3b) + ( -3a + 4b) + ( a-2b)=

Zad 2 Wykonaj odejmowanie i zredukuj wyrazy podobne:

a. 4a- ( -2a+3)=
b. -7x - ( 3y-4x-2)=
c. (4x - 7) -( 10x+2)=
d. ( 2a+3) - ( a-5)-(-2a+1)=
e. -(3x+2y-5)-(-4x+y+2)=

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-22T13:19:15+01:00
Zad 1 Wykonaj dodawanie i zredukuj wyrazy podobne:

a. 3ax + (2ax-5) = 3ax + 2ax + 5 = 5ax + 5 = 5(ax + 1)
b. -4x + ( -2x+3y-3)= -4x - 2x + 3y -3 = -6x + 3y - 3 = 3(-2x + y -1)
c. ( x-2y) + ( 5x-7y) = x-2y + 5x - 7y = 6x - 9y = 3(2x - 3y)
d. ( 2a+3b) + ( -3a + 4b) + ( a-2b) = 2a + 3b -3a + 4b + a - 2b = 5b

Zad 2 Wykonaj odejmowanie i zredukuj wyrazy podobne:

a. 4a- ( -2a+3)= 4a + 2a - 3 = 6a - 3
b. -7x - ( 3y-4x-2)= - 7x - 3y + 4x + 2 = -3x -3 y + 2
c. (4x - 7) -( 10x+2)= 4x - 7 - 10x - 2 = - 6x - 9
d. ( 2a+3) - ( a-5)-(-2a+1)= 2a + 3 - a + 5 + 2a - 1 = 3a + 7
e. -(3x+2y-5)-(-4x+y+2)= -3x - 2y + 5 + 4x - y - 2 = x - 3y + 3
1 1 1
2010-01-22T14:57:09+01:00
Zad 1 Wykonaj dodawanie i zredukuj wyrazy podobne:

a. 3ax + (2ax-5) = 3ax+2ax-5 = 5ax-5
b. -4x + ( -2x+3y-3) = -4x-2x+3y-3 = -6x+3y-3
c. ( x-2y) + ( 5x-7y) = x-2y+5x-7y = 6x-9y
d. ( 2a+3b) + ( -3a + 4b) + ( a-2b) = 2a+3b-3a+4b+a-2b = 5b

Zad 2 Wykonaj odejmowanie i zredukuj wyrazy podobne:

a. 4a- ( -2a+3) = 4a+2a-3 = 6a-3
b. -7x - ( 3y-4x-2) = -7x-3y+4x+2 = -3x-3y+2
c. (4x - 7) -( 10x+2) = 4x-7-10x-2 = -6x-9
d. ( 2a+3) - ( a-5)-(-2a+1) = 2a+3-a+5+2a-1 = 3a+7
e. -(3x+2y-5)-(-4x+y+2) = -3x-2y+5+4x-y-2 = x-3y+3
1 4 1